Spreading the Good Apples Out: Market Entry Dynamics of Quality-Differentiated Products - Esteban Jaimovich; Boryana Madzharova; Vincenzo Merella (CESifo GmbH, 2024)
This paper examines firms' market entry strategies for quality-differentiated goods, focusing on both initial and subsequent product-level entry decisions. Using a theoretical framework incorporating nonhomothetic preferences, we show that premium products are more likely to enter wealthier markets earlier, where producers can capture higher mark-ups. Furthermore, the determinants of follow-up market selection differ by product quality: for premium products, income plays a dominant role in shaping expansion paths, whereas geographic proximity remains the primary driver for low-quality products. Empirically, we test these predictions using micro-level data from the refrigeration industry. Our results confirm a strong positive relationship between market order of entry and income, with this effect being particularly pronounced for high-quality products. Additionally, we observe that, as product quality increases, follow-up markets tend to be geographically more dispersed relative to earlier markets.
Keywords: F10; F14; F23; L68; 330; market entry; gravity; nonhomothetic preferences; quality-differentiated products